Asuhan Keperawatan Pada TN. A Risiko Perilaku Kekerasan Dengan Fokus Tindakan Mengontrol Emosi :Terapi Relaksasi Napas Dalam di RSJ Dr. Soeharto Heerdjan Jakarta - Nur Syifa Qothrun Nada; Christina Trisnawati; Rahaju Ningtyas (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background : Mental health is a sentimental, psychological and social healthy condition that can be seen from satisfying relationships with others, effective behavior and handling, positive ideas and sentimental health. The possible problem that might arise is violent behavior, a condition where a person physically commits a dangerous act, either to another person or to himself. Based on Indonesian National data for 2017, patients with a risk of violent behavior are around 0.8% of 10,000 people. From these data it can be seen that the incidence of violent behavior is very high. Deep breathing is one of the interventions in treating patients with a risk of violent behavior. Deep breathing relaxation techniques can regulate emotions and maintain emotional balance, so that angry emotions are not excessive. Objective: Knowing the description of providing nursing care to patients at risk of violent behavior with a focus on controlling emotions: deep breathing relaxation techniques. Results: The results of nursing implementation state that patients at risk of violent behavior can understand the application of deep breathing relaxation techniques to control emotions.Conclusion: Patients at risk for violent behavior can apply deep breathing relaxation techniques to control their emotions.